Elemen-Elemen Bisnis pada PT. Sinar Jaya Megah Langgeng Menggunakan Model Bisnis - Jimmy Sentosa Sentosa (Jurnal Sekretaris dan Administrasi Bisnis, 2022)
Sinar Jaya Megah Langgeng is a transportation company that prioritizes inter-city inter-island services (AKAP). PT. Sinar Jaya Megah Langgeng has 36 years of experience and is one of the biggest companies in the transportation sector. In this study, the writer tries to see what business plan is being developed by PT. Sinar Jaya Megah Langgeng is seen from the theory of business elements on the business model canvas proposed by Osterwalder in his book entitled Business Model Generation. The author uses the canvas model in the analysis of the business plan of PT. Sinar Jaya Megah Langgeng because the canvas model is a simple model and has a flexible nature that is easy to modify while still providing a comprehensive view of the business model. The results of the study show that the Customer Segment are segmented model, Value Propositions which is given max value of Performance, Price, Accessbility and Convenience, Channels is used private vehicle, Customer Relationship developed is maintaining good relationship with the consumer, Revenue Stream comes from ticket sales, Key Resource which are owned by PT. Sinar Jaya Megah Langgeng are intellectual (SIUP), human (employees) financial and strategic locations, Key Activity is deliver customer to their destinations, Key Partners are ticket sales agent and online, Cost structure in this company are worker salary, maintenance cost, fuel cost, driver salary and sales commisions.